The analysis and prediction of crack growth in plate by using xfem method - Nguyễn Huỳnh Anh Tuấn; Nguyễn Hoài Sơn; Chương Thiết Tú (Journal of Technical Education Science, 2018)
Fracture Mechanics, which is a science subject, mainly studies about the durable longevity of materials, mechanical components or building components when they have a crack. The method helps quantify the relation between the materials ’nature, tension, and identify the presence of the crack which can destruct the structure and propagation mechanism of the cracks. The extended finite element method (XFEM) proposed by T. Belytschko in 1999 is regarded as a special cure to crack problems. This paper presents a method to identify cracks in the plates based on the analysis and prediction of crack growth by calculating the parameters of mechanical cracking such as the stress intensity factor, predicted path of the crack when the spread phenomenon appears.